Finnish parents’ perception of the impact of COVID-19 on the lives of autistic adolescents - Kwok Ng; Sanni Hiltunen; Marleena Pekonen; Eija Kärnä (Humanities & Social Sciences Communications)
Abstract The COVID-19 pandemic impacted autistic adolescents differently, but less is known about what aspects of their lives were the most affected. In this paper, we used a convenience sample (n = 323) of Finnish parents of autistic adolescents who reported the perceived impact of COVID-19 on the lives of their autistic children. Data were analysed with content analyses and four themes emerged; studies, everyday life, interaction, and personal matters. The impact was considered to have been more negative (69%) than positive (31%). There were some mixed feelings towards the impact of COVID-19 and these were targeted particularly towards the way studies were carried out. Parents reported temporal negative impact of the pandemic such as, overall quality of schooling, changes to daily routines, lack of friendships, and reduced mental health. These areas should be monitored post-pandemic. In addition, parents reported their autistic adolescents were able to learn in an undistracted way, were supported by their family, had less exposure to stressful stimuli. The parents appreciated the opportunity to see their autistic child thrive. These were important learnings for designing personalised education for autistic adolescents, such as hybrid schooling and flexible supportive environments in a post-COVID-19 lockdown world.